THE EFFECT OF PPE, EBITDA, AND THE AUDIT COMMITTEE ON AUDIT DURATION IN THE 10 LARGEST BANKS IN INDONESIA - Ricky Bryan D.P. Tampubolon; Rista Lintang Danang Kuncoro; Salgado Ginting Munthe; Muhammad Rizki Putra Pratama; Ahmad Pauzi Ridwan (Journal of Social and Economics Research, 2025)
This study examines the effect of Plant, Property, and Equipment (PPE), EBITDA, and the Audit Committee on audit duration in ten major banks in Indonesia during the 2022-2024 period using a quantitative approach. The study employs secondary data from audited annual financial statements and applies multiple linear regression analysis. The results show that PPE has a significant negative effect on audit duration, indicating that standardized and digitalized asset management in large banks improves audit efficiency. EBITDA does not have a significant effect on audit duration, while the Audit Committee has a positive and significant effect. Simultaneously, PPE, EBITDA, and the Audit Committee significantly influence audit duration, suggesting that asset characteristics and corporate governance mechanisms play an important role in determining audit completion time in large Indonesian banks.